Risk disclosures and firm value of tourism industry companies in Malaysia: the effect of COVID-19 / Barbara Belinda James - James, Barbara Belinda (2024)
Accounting scandals and the pandemic Covid-19 have had a significant impact on the firm’s value and shareholders, which becomes a concern for the risk related to the firms being investigated. The shareholders are external to the firms, so they can only refer to the firm’s Annual Reports to decide on their investment. The regulatory bodies, such as Bursa Malaysia and Financial Reporting Standard Board have published new requirements and standards to be followed by the firms. There is an urgent need for the firms to disclose not just their financial information, but also non-financial information such as their risk disclosures. Pandemic Covid-19 has increased the awareness of the business risks, especially for the firms in the tourism industry that have been affected the most during the pandemic. This study aims to investigate the level of risk disclosures and the impact of four categories of risk disclosures which are operational risk, financial risk, strategic risk, and environmental risk on firm value. This study is based on data obtained from the firms’ Annual Reports of tourism industry companies for the period of 5 years from 2017 to 2022 but excluding 2020 because all the firms did not publish their Annual Report in the year 2020 due to the outbreak of Covid-19. The data was analyzed to evaluate and determine the level of disclosures for three periods under study, which is Pre Covid-19 and Post Covid-19. This study found that the level of disclosures is at low level for operational risk and operational risk in the Pre Covid-19, and in the Post Covid-19, the disclosure level increases to moderate level. Strategic and environmental risks are still at a minimal level for both periods. This study also found that operational risk, strategic risk and environmental risk disclosures have a significant impact on the firm value in the Pre Covid-19 period. Meanwhile, the financial risk disclosures relationship with the firm value were not significant. In the Post Covid-19 period, there is no significant relationship between all categories of risk and the firm value. This study suggests that future research should be done on the impact of risk disclosures by categories so that the management of the firm will be aware of the importance of disclosing their related risk and its impact on their firm value. It is hoped that the study can contribute to the improvement in accounting standards and other accounting requirements, so that the information provided in the annual report will be useful and able to add value to the firm.